PRODUCTION PLANNING IN CONDITIONS OF MASS CUSTOMIZATION BASED ONTHEORY OF CONSTRAINTS - Janusz MLECZKO (Applied Computer Science, 2017)
In accordance with the requirements of the modern market, small and medium-sized enterprises (SMEs) need to offer a wide range of products tailored to the specific and individual requirements. The success of many enterprises, which work in mass production system and use economic effect of scale pro-duction slowly is a thing of the past. There are many enterprises, generally small and medium manufacturing in unit and small batch production, for which it is necessary to develop optimal methods of production planning, taking into account the flexible production requirements, matched to the time-varying customer’s demand. The article presents the production planning based on TOC in conditions of mass customization. Presented solutions are used in modern practice.